Unsaturated Shear Strength Assessment Based on Soil Index Properties - Fondjo, Armand Augustin; Theron , Elizabeth; Ray, Richard P. (Theory and Applications of Engineering Research Vol. 2, 2024)
The shear strength is a fundamental property of soil material. The measurement of the shear strength of unsaturated soils is challenging. Several tests are necessary to establish the strength variation with matric suction, and a long time is required to achieve the matric suction equilibrium in specimens before testing. Predictive models can evaluate the unsaturated shear strength of heaving soil. The research aims to develop models to determine the shear strength parameters of partly saturated soils. These include the angle of increase in shear strength with variation in matric suction (\(φ\)b), angle of internal friction related to net normal stress (\(φ\)'), and effective cohesion (c'). Soil properties were evaluated through particle size distribution, specific gravity, consistency limits, swelling test, modified Proctor compaction test, suction test, and advanced triaxial testing. Regression analysis was performed using MINITAB 20 Software to develop predictive models. The validation process includes the p-value, determination coefficient, comparing predicted with experimental values, and comparing other models in literature with models developed in this study. The engineered models can estimate the shear strength characteristics of compacted, unsaturated soils with acceptable precision.